2009
DOI: 10.1111/j.1440-1681.2008.05065.x
|View full text |Cite
|
Sign up to set email alerts
|

DESIPRAMINE‐INDUCED Ca2+‐INDEPENDENT APOPTOSIS IN MG63 HUMAN OSTEOSARCOMA CELLS: DEPENDENCE ON P38 MITOGEN‐ACTIVATED PROTEIN KINASE‐REGULATED ACTIVATION OF CASPASE 3

Abstract: 1. It has been shown that the antidepressant desipramine is able to induce increases in [Ca(2+)](i) and cell death in MG63 human osteosacroma cells, but whether apoptosis is involved is unclear. In the present study, the effect of desipramine on apoptosis and the underlying mechanisms were explored. It was demonstrated that desipramine induced cell death in a concentration- and time-dependent manner. 2. Cells treated with 100-800 mmol/L desipramine showed typical apoptotic features, including an increase in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…These findings are in agreement with previous studies which found that DMI inhibited cell proliferation and induced apoptosis in osteosarcoma cells, prostate cancer, colon cancer, renal tubular and glioma cells (14,15,(26)(27)(28)(29) and caused cell cycle arrest in colon cancer cells (13). In this study, we found a decrease in mRNA expression of Bcl-2 and survivin.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in agreement with previous studies which found that DMI inhibited cell proliferation and induced apoptosis in osteosarcoma cells, prostate cancer, colon cancer, renal tubular and glioma cells (14,15,(26)(27)(28)(29) and caused cell cycle arrest in colon cancer cells (13). In this study, we found a decrease in mRNA expression of Bcl-2 and survivin.…”
Section: Discussionsupporting
confidence: 83%
“…Associated with these changes was an inhibition of IκB degradation, NF-κB nuclear translocation and inhibition of phosphorylation of p38 MAP kinase, as would be predicted by the current study indicating an inhibition of TLR4 signaling by these tricyclics. In contrast, when tricyclics were studied in cells unlikely to express TLR4 or in cells stimulated by drugs acting through non-TLR4 pathways, tricyclics were reported to either have no effect on p38 MAP kinase (Chang et al, 2008) or to activate it (Otczyk et al, 2008, Lu et al, 2009), rather than inhibit it. These data are again not consistent with a direct inhibitory effect of tricyclics on p38 MAP or NF-κB independent of the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Tricyclic antidepressants (TCAs), such as amitriptyline and desipramine, which are commonly used to treat depression and chronic pain (Kirino and Gitoh, 2011;Dell and Butrick, 2006), also have antineoplastic activity in a wide variety of cancer cells, such as human colon cancer HT-29 cells, human osteosarcoma MG63 cells, human prostate cancer PC3 cells, rat glioma C6 cells, mouse skin squamous carcinoma (Ca3/7), and human multiple myeloma MM cells (Kabolizadeh et al, 2012;Lu. et al, 2009;Chang et al, 2008;Ma et al, 2011;Kinjo et al, 2010;Mao et al, 2011).…”
mentioning
confidence: 99%